PEMBANGUNAN HUKUM SUMBER DAYA AIR SUNGAI YANG BERBASIS KEARIFAN LOKAL: PELUANG DAN TANTANGANNYA - Mr. Sulastriyono (Fakultas Hukum Universitas Gadjah Mada, 2008)
This article aims to discuss the opportunity and challenge in the development of river water resources law as a consequence of population growth, development, and technology advancement. Fast growth on water needs induces the growth of economic value of water, rather than its social values. This condition potentially causes of conflict interests among sectors, among regions and among various stakeholder related to water resources management. The management of river water resources can be perceived as an opportunity as well as a challenge. The quantity and the potential of water which is abundant in Indonesia to use water resources optimally. However, the development of river water resources law still faces some challenges, namely institutional obstacle, legal system and culture. Globalization in the free market economic order must be faced by Indonesia in its efforts to develop law on the management of river water resources. Privatization in the management of river water resources led to the increase of the role of private sector in pursuing economic benefits. It is feared that privatization will limit the community access to water resources and will make the price of water is more expensive. An integrated law development of river water resources based on local wisdom is an alternative guarantee the community access and the sustainability of the availability way to river water resources.